Mengukur Keputusan Nasabah Melalui Analisis Brand Association Studi Kasus pada Bank Muamalat Indonesia â Cabang Bogor - Mubarak, Mumuh Mulyana; Puspitasari, Ratih (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
This research examines of the questions to (1) the customer behaviour in choosing variety of products offered by Bank Muamalat Indonesia in Bogor, (2) any factors that could be dominant and have an opportunity to be developed, (3) what kind of brand association that are formed by customers of Bank Muamalat Indonesia in Bogor. The main parameter in this research is based on The Respondent Characteristic Analysis and The Brand Association Analysis. The present study investigates that Security and Services could create a Brand Assocition of Bank Muamalat Indonesia in Bogor. Finally, those Five attributes will be set as an image to the customers to describe the Bank Muamalat Indonesia in Bogor. Keywords: Brand Association.